DESCRIPTION OF POST-PARTUM VISITS (KF1-KF4) FOR POSTPARTUM MOTHERS AT PAGEDONGAN COMMUNITY HEALTH CENTER IN 2025 - Nur Kamal, Maya Aulia; Feti Kumala Dewi; Arlyana Hikmanti; Nabila Anindya Putri Maheswari , (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: The postpartum period is a recovery phase after childbirth that requires continuous monitoring through postpartum visits to detect complications early and ensure maternal well-being. According to health service standards, postpartum visits are conducted four times, namely KF1, KF2, KF3, and KF4. These visits aim to monitor maternal health, support the recovery process, and provide health education and services during the postpartum period. Objective: To describe the coverage of postpartum visits (KF1–KF4) among postpartum mothers at the Pagedongan Community Health Center in 2025. Method: This study employed a quantitative descriptive design with a retrospective approach. The sample consisted of 410 postpartum mothers selected using a total sampling technique. Data were obtained from Maternal and Child Health (KIA) reports and maternal cohort registers. Data analysis was conducted using univariate analysis and presented as frequency distributions and percentages. Results: Most postpartum mothers were of healthy reproductive age (20–35 years), accounting for 313 respondents (76.3%), while 97 respondents (23.7%) were of unhealthy reproductive age (<20 years and >35 years). Based on parity, the majority were multiparous mothers (65.1%), followed by primiparous (24.1%) and grandemultiparous mothers (10.7%). Regarding education level, most respondents had primary education (62.9%), followed by secondary education (31.0%) and higher education (6.1%). The coverage of postpartum visits was very high, with KF1 attended by 410 mothers (100%), KF2 by 404 mothers (98.5%), KF3 by 403 mothers (98.3%), and KF4 by 400 mothers (97.6%). Conclusion: The coverage of postpartum visits among postpartum mothers at the Pagedongan Community Health Center in 2025 was classified as very good. High participation was observed at every stage of postpartum visits (KF1–KF4), indicating strong utilization of postpartum health services.